Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s00213-014-3576-4
|View full text |Cite
|
Sign up to set email alerts
|

The self-administration of rapidly delivered cocaine promotes increased motivation to take the drug: contributions of prior levels of operant responding and cocaine intake

Abstract: Rapid drug delivery augments the motivation for cocaine independently of effects on the levels of drug intake or operant responding for drug. We suggest that rapid delivery might increase the motivation for drug by promoting neuroplasticity within reward pathways. This neuroplasticity could involve increased regulation of BDNF/TrkB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 76 publications
2
18
1
Order By: Relevance
“…Finally, when the speed of i.v. drug injection is varied during LgA sessions, rats allowed to self-administer rapid cocaine injections (5 versus 90 s) subsequently show increased motivation to obtain the drug (Bouayad-Gervais et al, 2014 andMinogianis et al, 2013). This effect is illustrated in Fig.…”
Section: The Long-access Modelmentioning
confidence: 91%
See 3 more Smart Citations
“…Finally, when the speed of i.v. drug injection is varied during LgA sessions, rats allowed to self-administer rapid cocaine injections (5 versus 90 s) subsequently show increased motivation to obtain the drug (Bouayad-Gervais et al, 2014 andMinogianis et al, 2013). This effect is illustrated in Fig.…”
Section: The Long-access Modelmentioning
confidence: 91%
“…This prompted us and others to ask whether the speed of drug delivery plays a role in the propensity to escalate drug consumption. Work on this issue showed that when daily access to cocaine is increased from 1 to 6 h, rats given access to rapid (5-45 s) versus slower (90 s) injections of cocaine take more drug and are also more likely to escalate their consumption over days (Bouayad-Gervais et al, 2014, Minogianis et al, 2013and Wakabayashi et al, 2010. Fig.…”
Section: Bmentioning
confidence: 99%
See 2 more Smart Citations
“…administration experiments were based on used faster pumps that delivered 1.6 ml/minute [95], compared to ours that infuse drug at approximately 1.0 ml/minute. The relatively slow speed of the self-administration pumps could have lowered the efficacy of the cocaine delivery system, as faster speeds of delivery results in increased motivation during self-administration in rats [120,121] and humans [122,123]. This explains why all routes of cocaine absorption used by humans facilitate concentrated, rapid delivery of concentrated drug doses into the bloodstream [124,125].…”
Section: Discussionmentioning
confidence: 99%